A comparison of mandibular incisor proclination when using clear aligners and fixed labial orthodontic brackets - Hennessy, Joe (Trinity College (Dublin, Ireland). School of Dental Science, 2015)
The objective of this ‘2-arm parallel' clinical trial was to compare the mandibular incisor proclination produced by fixed labial appliances and 3rd generation clear aligners.
Keywords: Dental Science, D.Ch.Dent.; D.Ch.Dent Trinity College Dublin